(untitled) (Sains Humanika, 2015)
Malaysia Competition Act 2010 was introduced recently by the Malaysian government in 2010 which came into effect in 2012. Among the aim of the Competition Act 2010 is to encourage economic development via regulating competition process for commercial activity in Malaysia. As such, Malaysia Competition Commission was established under the Competition Commission Act 2010 to implement provisions contained in the Competition Act 2010. Since the Competition Act 2010 is new, it remains uncertain whether the provisions in the Competition Act 2010 affects ongoing business practices in Malaysia. Thus, the objective of this study is to identify provisions in the Competition Act 2010 which implicates commercial activity in Malaysia. Result of the study indicated that provisions relating to two main prohibitions contained in the Competition Act 2010, namely anti-competitive agreement and abuse of dominant position are applicable to various commercial activity in Malaysia. This study reveals that, although the Competition Act 2010 is silent on the detail application of its provisions in specific commercial sector,yet it provides general outline to be applied to all types of commercial activity in Malaysia.Â